Integrative performance practice and theory for the interdisciplinary performer - Bryon, Experience (Routledge, 2014)
"Integrative Performance serves a crucial need of 21st-century performers by providing a transdisciplinary approach to training. Its radical new take on performance practice is designed for a climate that increasingly requires fully rounded artists. The book critiques and interrogates key current practices and offers a proven alternative to the idea that rigorous and effective training must separate the disciplines into discrete categories of acting, singing, and dance. Experience Bryon's Integrative Performance Practice is a way of working that will profoundly shift how performers engage with their training, conditioning and performance disciplines. It synthesizes the various elements of performance work in order to empower the performer as they practice across disciplines within any genre, style or aesthetic. Theory and practice are balanced throughout, using: - Regular box-outs, introducing the work's theoretical underpinnings through quotes, case studies and critical interjections. - A full program of exercises ranging from training of specific muscle groups, through working with text, to more subtle structures for integrative awareness and presence. This book is the result of over twenty years of practice and research working with interdisciplinary artists across the world to produce a training that fully prepares performers for the demands of contemporary performance and all its somatic, emotive and vocal possibilities"--Provided by publisher.